Probleme beim Nachschlagen der Entsprechungen von Kurzwörtern und Abkürzungen deutscher Stellenangebote mithilfe digitaler Hilfsmittel und deren Einfluss auf den Rekrutierungsprozess - Sekuła, Justyna Katarzyna (Comparative Legilinguistics, 2025)
The aim of this article is to demonstrate possible problems in finding the equivalents of acronyms and abbreviations of German job vacancies with the help of digital translation aids, which are relevant for the understanding of job vacancies by those who may apply for a position. In addition, the issue of the impact of the wrong development of acronyms and abbreviations by means of digital translation aids on the understanding of job offers by job applicants and the subsequent recruitment process is addressed.